THE GAMES AND THEIR RELATIONS ON THE EDUCATION FOR THE HEALTH OF KAINGANG INDIGENOUS PEOPLES OF PARANÁ (Fiep Bulletin - online, 2011)
The University without Borders program, developed by the Ministry of Science, Technology and Higher Education of Paraná, holds the project "Relashionship between University and Indigenous Education with focus on Education for Health and Environment", prepared and executed by a multidisciplinary team composed of educators, recently graduated professionals and students of UNICENTRO / G. This article examines aspects of the Marrecas and Ivaí indigenous people realities, describes the methodology used by the involved in the project, with a dynamic focused on the realization of intervention activities for the health education and environment, using the practice of recreational games, competitive and cooperative, in a inclusive manner.
Keywords: Healh; Games; Kaingang Indigenous people